2002
DOI: 10.1038/sj.bmt.1703736
|View full text |Cite
|
Sign up to set email alerts
|

Successful non-T cell-depleted HLA haplo-identical three-loci mismatched hematopoietic stem cell transplantation from mother to son based on the feto-maternal microchimerism in chronic myelogenous leukemia

Abstract: A 17-year-old male with chronic myelogenous leukemia in blast crisis received a non-T cell-depleted (TCD) HLA haplo-identical three-loci mismatched hematopoietic stem cell transplant (HSCT) from his mother. Long-term feto-maternal microchimerism was detected by nested polymerase chain reaction with sequence-specific primer typing. The post-transplantation prophylaxis against graft-versus-host disease (GVHD) was tacrolimus with minidose methotrexate. Sustained engraftment was obtained. Acute GVHD (grade 2) deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…The rapid regression of chemoresistant disease was also reported in a case of CML in blast crisis after HSCT from an HLA-haploidentical mother with long-term fetomaternal microchimerism. 6 This case strengthens the hypothesis that the persistence of immunotolerance to IPA has a beneficial inhibitory effect on GVHD following blood stem cell transplants from microchimeric mothers. A prospective study will be needed to elucidate the role of long-term fetal cell microchimerism in selecting an HLA-haploidentical mother as an alternative donor for hematopoietic stem cell transplantation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The rapid regression of chemoresistant disease was also reported in a case of CML in blast crisis after HSCT from an HLA-haploidentical mother with long-term fetomaternal microchimerism. 6 This case strengthens the hypothesis that the persistence of immunotolerance to IPA has a beneficial inhibitory effect on GVHD following blood stem cell transplants from microchimeric mothers. A prospective study will be needed to elucidate the role of long-term fetal cell microchimerism in selecting an HLA-haploidentical mother as an alternative donor for hematopoietic stem cell transplantation.…”
Section: Discussionsupporting
confidence: 70%
“…2,3 Recent reports, however, have questioned the feasibility of hematopoietic stem cell transplantation (HSCT) without T-cell depletion (TCD) from an HLA-mismatched mother or sibling in the presence of long-term feto-maternal microchimerism. [4][5][6] We performed a successful blood stem cell allograft from a two-locus mismatched haploidentical mother based on long-term feto-maternal microchimerism in a patient with refractory acute lymphoblastic leukemia (ALL).…”
mentioning
confidence: 99%
“…The detailed clinical course of 8 of these patients was previously reported in several papers. [25][26][27][28][29] The eligibility criteria for the study were as follows: (1) having advanced leukemia or lymphoma; (2) receiving T cell-replete bone marrow and/or peripheral blood stem cell (PBSC) grafts mismatched for 2 or 3 HLA-A, -B, or -DR antigens in the GVH direction harvested from mother, offspring (to mother), or an NIMA-mismatched sibling who was shown to have recipient-specific microchimerism presumed to be of fetal or maternal origin; (3) receiving tacrolimus-based GVHD prophylaxis. Using a standardized questionnaire form, participating centers were requested to consecutively report data with respect to the patient/donor characteristics and clinical outcomes in terms of neutrophil recovery, platelet recovery, aGVHD, chronic GVHD (cGVHD), graft failure, relapse, and survival after transplantation to the office of the Japanese Collaborative Study Group for NIMA-Complementary Haploidentical Stem Cell Transplantation (Department of Hematology/Oncology, Kyoto University Hospital, Japan).…”
Section: Study Patients and Data Collectionmentioning
confidence: 99%
“…Microchimerism of donor's alleles in the recipient were detected before and long after the infusion, prompting them to speculate that the mother had been tolerant to the inherited paternal antigens (IPAs); thus, the infused effector lymphocytes from her daughter survived longer in the face of the maternal immune system. Soon thereafter, Ochiai et al 21 reported a case of non-T cell-depleted mother-tochild HSCT from his microchimeric mother. Although the mother and son had serologic mismatches at HLA-A, -B, and -DR in the graft-versus-host direction, acute GVHD was restricted to skin and rapidly improved after standard therapy.…”
Section: Introductionmentioning
confidence: 99%